“Language Barriers in the Emergency Centre (EC): A survey of secondary public hospital EC doctors on the perceived presence and impact of language barriers" - Docrat, Nasreen (Division of Emergency Medicine, 2021)
Background Communication is vital to patient-doctor interactions especially in emergency centres (EC). It is evident from international and South African studies that language barriers result in suboptimal clinical outcomes, increased use of already limited resources and poor patient satisfaction. In the Western Cape, initiatives such as community trained interpreters, telephonic services and multilingual language policies have been implemented to improve communication between doctors and patients. Objectives This study was done to ascertain to what extent language barriers are perceived to still exist by doctors in emergency centres in secondary public hospitals in Cape Town. Methods A quantitative on-line survey of full time doctors in the ECs of six urban secondary public hospitals in Cape Town was conducted in October 2019. Data was collected over a 5 week period and covered demographics, languages spoken, (self-reported) fluency of languages spoken, languages encountered, perceived occurrence of language barriers, perceived impact of language barriers and strategies currently implemented to overcome these barriers. Results Of the 119 doctors invited to complete the survey, 74 eligible responses were received. Language barriers still exist in secondary public hospitals in the Western Cape. The majority of doctors spoke Afrikaans and no isiXhosa speaking doctors took part in the survey. Half of the doctors surveyed stated they would not be able to take a history in isiXhosa without an interpreter. Most (97%) of doctors had not heard of community trained interpreters and only 23% had ever used the telephone interpretation service available. Perceived consequences of language barriers include: inability or longer duration to get a history, increased use of resources, and patients returning because they did not fully understand the treatment plan. Informal interpreters such as nursing staff and family members were used most often to overcome language barriers. No official interpreters were available to assist in person and doctors are either unaware of telephonic interpreting services or woefully under-using this service. Due to language barriers, doctors are left feeling frustrated with themselves or sad for the patients that they are meant to be helping due to language barriers. Conclusion Reintroduction of community based interpreters, teaching doctors more languages and investment into technologyaided translation services are possibilities that have been suggested by doctors and could be researched further to help improve the current situation.